2014
DOI: 10.1038/ncomms4116
|View full text |Cite
|
Sign up to set email alerts
|

Kinase fusions are frequent in Spitz tumours and spitzoid melanomas

Abstract: Spitzoid neoplasms are a group of melanocytic tumours with distinctive histopathological features. They include benign tumours (Spitz naevi), malignant tumours (spitzoid melanomas) and tumours with borderline histopathological features and uncertain clinical outcome (atypical Spitz tumours). Their genetic underpinnings are poorly understood, and alterations in common melanoma-associated oncogenes are typically absent. Here we show that spitzoid neoplasms harbour kinase fusions of ROS1 (17%), NTRK1 (16%), ALK (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
556
4
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 548 publications
(616 citation statements)
references
References 44 publications
29
556
4
8
Order By: Relevance
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13). In a rapidly evolving scenario, these findings indicate that TRKA inhibition may represent an innovative opportunity for the therapy of selected patients whose tumors harbor NTRK1 gene rearrangements and this has supported the enrollment of TRKA-positive patients in ongoing clinical trials of entrectinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13). In a rapidly evolving scenario, these findings indicate that TRKA inhibition may represent an innovative opportunity for the therapy of selected patients whose tumors harbor NTRK1 gene rearrangements and this has supported the enrollment of TRKA-positive patients in ongoing clinical trials of entrectinib.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a rapidly evolving landscape, large-scale sequencing efforts have led to identification of additional chromosomal rearrangements involving NTRK1 as well as NTRK2 and NTRK3, the genes which respectively encode the TRKA, TRKB, and TRKC proteins, in further tumor types (14)(15)(16)(17). These findings provide a strong rationale for the development of TRK kinase inhibitors in several distinct selected patient populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that over 50% of Spitz nevi harbor fusions involving the kinases ALK, ROS1, NTRK1, BRAF, and RET. 32 Those tumors with ALK rearrangement (~10%) show corresponding overexpression of ALK by immunohistochemistry. The ALK fusion partners in Spitz Modern Pathology (2015) 28, 904-912 ALK in epithelioid fibrous histiocytoma nevi have been identified as TPM3 (tropomyosin 3) and DCTN1 (dynactin 1).…”
Section: Discussionmentioning
confidence: 99%
“…48 A subset of somatic atypical spitzoid tumors (28%) showed loss of BAP1 expression and concomitant BRAF mutations. 49 These molecular alterations are not diagnostic for a melanoma and FISH assays are not applied for the detection of kinase gene fusions in the current diagnostic algorithm for atypical spitzoid tumors.…”
Section: Array-based Comparative Genomic Hybridizationmentioning
confidence: 99%